Addition of ammonium hydroxide as formaldehyde scavenger for sesenduk (Endospermum diadenum) wood compregnated using phenolic resins - Ashaari, Zaidon; Lee, Seng Hua; Abdul Aziz, Mohd Hafifuddin; Nordin, Muhamad Norfazimie (Springer, 2016)
Compregnated sesenduk (Endospermum diadenum) was produced using low and medium molecular weight phenol formaldehyde resin. 0, 1, 1.5 and 3 % of aqueous ammonium hydroxide (NH3·H2O) were incorporated into the resin to act as formaldehyde scavenger. A maximum of 85.7 % reduction in formaldehyde emission was recorded, but the mechanical and physical properties of the treated sesenduk wood were negatively affected by the ammonium hydroxide addition.